2020
DOI: 10.3389/fphar.2020.593832
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Stimulates Macrophage-Mediated Clearance of Senescent Skin Cells Through Activation of the AKT2 Signaling Pathway by CD36 and RAGE

Abstract: Background: Macrophages can selectively recognize and eliminate senescent cells, but this function is impaired with age, resulting in excessive accumulation of senescent cells in the skin, which ultimately causes skin aging. Therefore, enhancing the immune surveillance ability of macrophages to clear senescent keratinocytes and fibroblasts from aging skin may be an effective skin rejuvenation strategy.Methods: In this study, a macrophage and senescent skin cell co-culture model was established whereby THP-1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In this study, we demonstrated that the phagocytic activity of RAW264.7 cells was increased by balenine treatment. Consistent with our results, it was reported that carnosine, an imidazole peptide, could enhance the phagocytic activity of macrophages through an activation of the AKT2 signaling pathway by CD36, a membrane protein that facilitates fatty acid uptake, and RAGE, a receptor for advanced glycation end products, to eliminate senescent skin cells [ 19 ]. However, further studies are required to identify the mechanism of phagocytosis activity by balenine treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we demonstrated that the phagocytic activity of RAW264.7 cells was increased by balenine treatment. Consistent with our results, it was reported that carnosine, an imidazole peptide, could enhance the phagocytic activity of macrophages through an activation of the AKT2 signaling pathway by CD36, a membrane protein that facilitates fatty acid uptake, and RAGE, a receptor for advanced glycation end products, to eliminate senescent skin cells [ 19 ]. However, further studies are required to identify the mechanism of phagocytosis activity by balenine treatment.…”
Section: Discussionsupporting
confidence: 92%
“…It was recently reported that the treatment of carnosine can promote the phagocytic capacity of macrophages to eliminate senescent skin cells [ 19 ]. Given the importance of phagocytic modulation by active compounds such as peptides, balenine may also regulate immune responses to clear degenerated organs.…”
Section: Introductionmentioning
confidence: 99%
“…During the last 5 years, the ability of CAR to modulate different activities of immune cells such as macrophages has been demonstrated [ 16 , 17 ]. It has been demonstrated that the interaction of CAR with particular receptors on the cell membrane could modify macrophage function by enhancing their phagocytotic activity [ 18 , 19 ]. It has also been demonstrated that HD can influence NO production and macrophage polarization [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune homeostasis function of macrophages is impaired with age, resulting in the decline of its selective scavenging ability to aging cells. This will contribute to the abnormal accumulation of senescent cells in skin [ 166 ]. However, there is little research on how UV-induced senescent cells bypass immune clearance.…”
Section: Evs In Aging-related Diseasesmentioning
confidence: 99%